The new ball menre tradition in Abbanuange village, Lilirilau sub-district, Soppeng district - St. Junaeda, St. Junaeda; Tenriwaru, Andi (Kampret Journal, 2024)
This research aims to: (1) determine the process of the new ball menre tradition in Abbanuange Village, Lilirilau District, Soppeng Regency, (2) determine the values ​​contained in the new ball menre tradition in Abbanuange Village, and (3) describe the community's views on the new ball menre tradition . This research is descriptive research using qualitative data. Data was obtained by making observations related to this tradition, conducting interviews with eight informants and documenting in the form of photos related to the procession of the new ball menre tradition. The results of this research show that: (1) The process of implementing the new menre bola tradition  has five stages, namely mattanra esso (determining a good day), naccenneri bola'e (rotating around the house), menre bola, barazanji, and maccera bola, (2) The values ​​contained in Tardidi Menre Baru Bola include the value of friendship, the value of aqidah, the value of morals, and the value of mutual cooperation, and (3) In this case there are different views of society, society in general still believes in the benefits that can be obtained. in implementing the new football menre tradition. Some people also think that this ritual is an ancient habit of parents that needs to be preserved, regarding whatever happens after the ritual is under the power of Allah SWT. Apart from that, there are some people who think that this is not in line with religious teachings, so it needs to be corrected or abandoned.